Treatment of anaplastic glioma - Wick, Wolfgang; Wiestler, Benedikt; Platten, Michael (Current understanding and treatment of gliomas, 2015)
Anaplastic gliomas have received increasing attention over the past years. As opposed to glioblastoma, where the focus has been on the evaluation of novel compounds (with mainly disappointing results), in anaplastic gliomas relevant progress was generated with genotoxic therapies and translational work on biomarkers. Anaplastic gliomas are classified using single biomarkers, namely isocitrate dehydrogenase (IDH) or the related CpG island methylator phenotype (CIMP), alpha-thalassemia/mental retardation syndrome X-linked (ATRX), telomerase reverse transcriptase (TERT), p53, 1p/19q, and O6-methylguanine DNA-methyltransferase (MGMT). With these molecular biomarkers, three main prognostically distinct groups have been defined: (i) CIMP-negative anaplastic gliomas, which have a similar prognosis as glioblastoma, (ii) CIMP-positive 1p/19q intact, and (iii) CIMP-positive 1p/19q codeleted gliomas. In the CIMP-negative, mainly IDH wild-type group, MGMT promoter methylation may be used to identify patients who benefit from alkylating chemotherapy. The mutually exclusive ATRX losses and 1p/19q codeletions are used to subcategorize anaplastic tumors with a mixed histology according to microscopic features. This eliminates the biological basis and clinical necessity for the diagnosis of mixed gliomas (anaplastic oligoastrocytomas). Retrospective long-term analysis of the EORTC 26951 and RTOG 9402 trials revealed that patients with tumors harboring 1p/19q codeletions benefit from addition of procarbazine, lomustine, and vincristine (PCV) chemotherapy to primary radiotherapy. RTOG 9402 suggests that this may be the case also for patients with 1p/19q intact tumors, but IDH mutation. Future developments in addition to the ongoing CATNON and CODEL trials, will focus on further refinement of the molecular predictors and development of treatments that not only increase survival but also maintain neurological function, cognition, and health-related quality of life.